Respuesta :

Answer: 144

Step-by-step explanation:

The binomial is  [tex]\left( 4x+3y\right)^3[/tex]

The expansion of [tex]\Rightarrow \left ( a+b \right )^n=^nC_0\left ( a \right )^n\left ( b \right )^0+^nC_1\left ( a \right )^{n-1}\left ( b \right )^1+^nC_2\left ( a \right )^{n-2}\left ( b \right )^2+^nC_3\left ( a \right )^{n-3}\left ( b \right )^3+\ldots[/tex]

Expansion of [tex]\left( 4x+3y\right)^3[/tex]

[tex]\Rightarrow ^3C_0\left ( 4x\right )^{3}\left ( 3y\right )^0+^3C_1\left ( 4x\right )^{2}\left ( 3y\right )^1+^3C_2\left ( 4x\right )^{1}\left ( 3y\right )^2+^3C_3\left ( 4x\right )^{0}\left ( 3y\right )^3[/tex]

So, the second term is

[tex]\Rightarrow ^3C_1\left ( 4x\right )^{3-1}\left ( 3y\right )^1\\\Rightarrow ^3C_1\left ( 4x\right )^{2}\left ( 3y\right )^1[/tex]

Its Coefficient is

[tex]\Rightarrow ^3C_1\times 4^2\times 3\\\Rightarrow 3\times 16\times 3=144[/tex]